2017
DOI: 10.1177/0748233717718973
|View full text |Cite
|
Sign up to set email alerts
|

The effect of tannic acid on bone mechanical and geometric properties, bone density, and trabecular histomorphometry as well as the morphology of articular and growth cartilages in rats co-exposed to cadmium and lead is dose dependent

Abstract: Cadmium (Cd) and lead (Pb) are toxic elements that accumulate to the largest extent in bones. Rats were used to investigate whether tannic acid (TA; 0.5%, 1.0%, 1.5%. 2.0%, or 2.5%) would have a protective effect on the structure and properties of bones in the case of exposure to Cd and Pb (diet: 7 mg Cd/kg and 50 mg Pb/kg) for 6 weeks. The effects of administration of TA in Cd- and Pb-poisoned rats on bone characteristics and the morphology of articular and growth cartilages were determined. All the rats admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 38 publications
1
16
0
Order By: Relevance
“…These metals tend to accumulate in calcified tissues 64,65 and this accumulation coincides with the reduction in the concentration of Ca in bone, which, in turn, leads to a reduction in the mechanical resilience of the bone. Cd, for example, induces bone loss and creates osteoporotic symptoms in bone following environmental levels of exposure, 66 while Pb equally reduces the bone Ca content, 67 similar to the effects observed in this study (Fig. 2).…”
Section: Resultssupporting
confidence: 86%
“…These metals tend to accumulate in calcified tissues 64,65 and this accumulation coincides with the reduction in the concentration of Ca in bone, which, in turn, leads to a reduction in the mechanical resilience of the bone. Cd, for example, induces bone loss and creates osteoporotic symptoms in bone following environmental levels of exposure, 66 while Pb equally reduces the bone Ca content, 67 similar to the effects observed in this study (Fig. 2).…”
Section: Resultssupporting
confidence: 86%
“…Kim et al ( 1998 ) demonstrated that the tissues of mice poisoned with 20 mg Cd per kg of body weight contained less Cd if the mice drank a water-based solution containing 0.5, 1.0 or 2.0 mg of tannic acid/ml. The use of a 2% tannic acid solution in rats receiving 7 mg Cd and 50 mg Pb/kg of feed or one litre of distilled water contributed to a significant decrease in the accumulation of those toxic metals in the hearts, lungs, tibia and blood compared to rats drinking water (Winiarska-Mieczan et al 2013 ; Winiarska-Mieczan 2013 ; Tomaszewska et al 2017a , b ). Studies showed that Pb was a more resistant metal than Cd to being bound by tannic acid (Winiarska-Mieczan 2013 ), where the use of 0.5, 1, 1.5 or 2% tannic acid solutions in adult rats simultaneously exposed to Cd and Pb resulted in a statistically significant reduction of Cd absorption in brains by 20–25% after 6 weeks of the experiment and about 35% after 12 weeks.…”
Section: Protective Effect Of Tea On Organisms Exposed To CD and Pbmentioning
confidence: 99%
“…Mineralization is an important parameter in the evaluation of bone quality and strength. In our study, the decrease in the percentage of nonorganic components and ash weight/dry weight ratio of femurs in animals exposed to Cd clearly demonstrate bone demineralization, consistent with findings obtained in other animal models of Cd toxicity and with reduced bone levels of Ca that is the main structural component of the extracellular matrix and a depot of this mineral for the whole organism . However, bone proprieties also depend on organic components of the matrix and our results demonstrate that a low‐dose chronic exposure to Cd significantly decreases the percent of such components.…”
Section: Discussionmentioning
confidence: 98%